Obstetric complications and advanced maternal age - Cabrera Ramos, Santiago G. (2023)
Advanced maternal age is directly proportional to the risk of obstetric and nonobstetriccomplications during gestation, both for the pregnant woman and thefetus. This is particularly important because the fertility rates of older women haveincreased. In the US, 10% of first births and 20% of all births occur to women 35years of age or older. Historically, advanced maternal age has been defined as anage greater than or equal to 35 years, a cutoff point that is supported by decliningfertility and the increased risk of genetic abnormalities in the offspring of womenolder than this age. However, the effects related to increasing age are continuousand the risk is greater the older the age at conception rather than as an effect ofpassing the 35 years threshold. Research has shown that older pregnant womenare at increased risk of early pregnancy complications such as miscarriage, ectopicpregnancy, chromosomal abnormalities and congenital malformations, as well as,preeclampsia, gestational diabetes, placental pathology, preterm delivery, low birthweight, perinatal mortality, multiple pregnancy, dystocic delivery, cesarean deliveryand maternal mortality. This article reviews recent publications on the subjectand includes statistics from a major hospital in Lima, Peru, and from the NationalDemographic and Family Health Survey - ENDES, 2022.